An Analytical Algorithm for Extracting Model Parameters in a Lumped-Parameter Equivalent Circuit of Solar Cells - Yunhan Ma; Jingxian Liu; Junkai Huang; Wanling Deng (Energies, 2022)
An analytical algorithm is proposed to extract model parameters in a single-diode lumped-parameter equivalent circuit of solar cells. In the calculation process, six relevant factors in the datasheet are necessary to establish a set of transcendental equations. This set of equations is analyzed and solved to acquire accurate values for the model parameters, by retaining equation items with important physical significance. Furthermore, based on simulations and reconstruction experiments, verifications show the accuracy and universality of the algorithm. Therefore, the proposed algorithm can be regarded as a valid solution for estimating the model parameters of a single-diode lumped-parameter circuit of solar cells.